Effect of Origanum vulgare Essential Oil Supplementation on the Advanced Parameters of Mobility and on the Integrity of Human Sperm DNA - Mbaye, Modou M.; El Khalfi, Bouchra; Ouzamode, Saida; Saadani, Brahim; Louanjli, Noureddine; Soukri, Abdelaziz (International Journal of Reproductive Medicine, 2020)
The reduced sperm mobility is one of the most important causes of male infertility. Several reports have indicated that the treatment of subnormal sperm samples with certain agents prior to artificial insemination significantly improves the fertilizing potential of sperm. We have among others some stimulants such as pentoxifylline, relaxin, prostaglandin E, and diltiazem. In our precedent work, we had tested the effect of supplementation with three essential oils, namely, sage (Salvia officinalis), oregano (Origanum vulgare), and eucalyptus (Eucalyptus globulus), on sperm cell mobility and vitality. Oregano oil had shown interesting biological properties by giving the best values of progressive mobility and vitality. In this study, we aim to verify the effect of oregano oil supplementation on the advanced parameters of mobility and on the integrity of the sperm DNA of 25 male infertile volunteers. Our results showed that oregano oil over an incubation period of 5 to 10 min of exposure significantly improves the advanced parameters of mobility, namely, curvilinear velocity (VCL), linear velocity (VSL), the mean velocity of the path (VAP), and the amplitude of the displacement (ALH). The effect of the increase in the VCL decreased the linearity (LIN), the mean line (STR), and the mean wobble (WOB). Oregano oil at 5 min had no significant effect on the DNA fragmentation index (DFI) and sperm decondensation index (SDI). However, at 10 min, it had a significant effect on both DFI and SDI. The analysis of our results showed that this plant oil rich in terpenoids and phenolic antioxidants could be a quite good in vitro additive with high potential for the world of medically assisted reproduction.